Formalization of Islamic Law in Indonesia in the Framework of Social Engineering Theory by Roscoe Pound - Zainal Muttaqin (El-Mashlahah, 2021)
Law has a very important role in people's lives. And, the law is assumed to have multifunctionality for the goodness of the community itself to achieve justice, legal certainty, orderly, advantages, and others. However, along with changes of time, the changes occur in people's lives that lead the law, as a binding norm, also changes following the harmony with the good of the community itself. In Indonesia, Islamic law as one of the sources of law and a living law has a role in social engineering efforts towards a better life for Indonesian people. Therefore, the problem is, how Islamic law can be a means for social engineering? The answer is, Islamic law can be a means of social engineering by becoming a positive law into legislation. Here, the formalization of Islamic law is urgent. But, the formalization must manifest in form of transformation and internalization of the values contained in Islamic law into the national law. Islamic law is not a static norm but a norm that can perform the dynamizing thought and engineering people's political behavior in realizing their ideals